Secure Key Management Schemes for High-Mobility VANET Environments - El-Dalahmeh, Moawiah; El-Dalahmeh, Adi (SOTVI, 2025)
Secure key management remains a critical challenge in Vehicular Ad Hoc Networks (VANETs) due to high mobility, rapid topology changes, latency constraints, and intermittent connectivity. Traditional key management techniques designed for static networks inadequately address these dynamic VANET characteristics, resulting in compromised security, scalability, and performance. Additionally, emerging quantum computing capabilities pose significant threats to classical cryptographic algorithms, necessitating the integration of quantum-resistant methods. To tackle these issues, this study proposes a hierarchical hybrid key management scheme tailored explicitly for high mobility VANET scenarios. The proposed approach combines symmetric, asymmetric, and lattice-based post-quantum crypto graphic methods within a dynamic clustering framework. Vehi cles dynamically form clusters based on proximity and mobility, wherein cluster heads efficiently distribute symmetric keys to reduce computational overhead and latency. For inter-cluster and vehicle-to-infrastructure communications, asymmetric cryp tography and lattice-based quantum-resistant algorithms en hance security and resilience against quantum threats. Extensive simulations using realistic mobility models (SUMO integrated with NS-3) demonstrate significant improvements over existing schemes. The results indicate reductions of approximately 30 40% in key distribution latency and up to 30% in computational overhead, alongside robust scalability with increasing vehicle den sity. Moreover, the incorporation of post-quantum cryptography ensures future-proof security. This paper identifies open research challenges, including adaptive security management, blockchain integration, and compatibility with emerging communication standards, providing valuable insights for future developments in secure and efficient VANET key management.